Psychometric Validation of the Self-Care Self-Efficacy Scale in Individuals With Inflammatory Bowel Disease - Francesca Trotta; Francesco Petrosino; Daniele Napolitano; Alessio Lo Cascio; Silvia Cilluffo; Mattia Bozzetti; Gianluca Pucciarelli; Ercole Vellone; Davide Bartoli (Gastroenterology Nursing, 2026)
This study was conducted to assess the psychometric properties of the Self-Care Self-Efficacy Scale and determine its validity and reliability in measuring self-efficacy related to self-care among individuals with inflammatory bowel disease (IBD). A multicenter, cross-sectional study was conducted across nine specialized IBD centers in Italy. Participants completed the Self-Care Self-Efficacy Scale and provided sociodemographic and clinical information. Confirmatory factor analysis was conducted to evaluate factorial validity. Reliability was assessed through McDonald’s Omega, composite reliability, and factor score determinacy. A total of 456 patients were included (mean age 43.49 ± 16.39 years; 49% women). Confirmatory factor analysis supported a unidimensional structure. The Self-Care Self-Efficacy Scale showed excellent internal consistency (ω = 0.90), strong composite reliability (0.88), and high factor score determinacy (0.92). All corrected item-total correlations exceeded 0.30, supporting adequate item discrimination. The Self-Care Self-Efficacy Scale was found to be a valid and reliable instrument for assessing self-efficacy in IBD self-care. Its brevity (10 items) makes it feasible for both clinical and research use, allowing identification of patients with low self-efficacy and supporting tailored interventions to enhance self-care, symptom control, and quality of life.